Performance analysis of multi-relay DF cooperative communication system based on directional antenna - Mingwei WANG; Huisheng ZHANG; Lixin LI; Lifeng HE (Dianxin kexue)
In order to achieve reliable communication in multi-relay cooperative communication，the directional antenna combining multi-relay cooperative communication system and optimal relay selection decode-and-forward cooperative strategy was presented.Firstly，the theoretical closed form of outage probability of the communication system using directional antenna operating in the three modes of DT-DR，DT-OR and OT-OR were presented.Then for three kinds mode，the collaboration communication system interrupt probability and signal-to-noise ratio，the number of relay nodes，the antenna gain channel fading efficiency and relationship between the channel capacity were analyzed in numerical simulation.These findings reveal that excellent performance of cooperative communication system with directional antennas could be achieved such as smaller outage probability and improved by best relay nodes and optimal power allocation coefficient.